Antiviral Efficacy of Verdinexor In Vivo in Two Animal Models of Influenza A Virus Infection - Perwitasari, Olivia; Johnson, Scott; Yan, Xiuzhen; Register, Emery; Crabtree, Jackelyn; Gabbard, Jon; Howerth, Elizabeth; Shacham, Sharon; Carlson, Robert; Tamir, Sharon; Tripp, Ralph A. (PLOS ONE, 2016)
Influenza A virus (IAV) causes seasonal epidemics of respiratory illness that can cause mild to severe illness and potentially death. Antiviral drugs are an important countermeasure against IAV; however, drug resistance has developed, thus new therapeutic approaches are being sought. Previously, we demonstrated the antiviral activity of a novel nuclear export inhibitor drug, verdinexor, to reduce influenza replication in vitro and pulmonary virus burden in mice. In this study, in vivo efficacy of verdinexor was further evaluated in two animal models or influenza virus infection, mice and ferrets. In mice, verdinexor was efficacious to limit virus shedding, reduce pulmonary pro-inflammatory cytokine expression, and moderate leukocyte infiltration into the bronchoalveolar space. Similarly, verdinexor-treated ferrets had reduced lung pathology, virus burden, and inflammatory cytokine expression in the nasal wash exudate. These findings support the anti-viral efficacy of verdinexor, and warrant its development as a novel antiviral therapeutic for influenza infection.